Factors influencing psychological well-being and gender among private financial sector employees in Malaysia - Shahrimin Adam Assim, Mohd Ibrani; Munusamy, Agilan; Yaccob, Yasmin; Mat Jusoh, Nurul Hidayu; Janis, Salina (Human Resource Management Academic Research Society, 2021)
This study examined the effect of coping strategy towards the relationship of psychology hardiness, well-being and gender among private financial institution sector employees in Malaysia. Correlations and differences pertaining to gender were also determined. A total of 141 employess from eleven private financial institutions in Malaysia participated in this study. A cross-sectional and correlational research design was employed. Psychology hardiness was measured using the dispositional Resilience [DRS-15 (v3.2)] scale, Coping strategy was measured using the Problem Oriented Brief Coping Experienced (BRIEF COPE) scale while Psychology well-being was measured using Well-being Manifestation Measure scale (WBMMS) scale. All hypotheses were tested and the results revealed that Coping Strategy had a significant role as a moderating variable. Further research is suggested to explore other possible moderating effects on psychology hardiness and well-being of banking employees in other domains of psychological attributes.